Estudio de prefactibilidad para la instalación de una planta productora de destilado de uva quebranta añejo - Quezada Oyarce, Raúl Arturo (2019)
This research project analyzes the viability to install a plant of Old Quebranta grapes distillate, which is been elaborated and aged in Oak barrels; providing the product a characteristic wood color and flavor. The product is aimed to the Metropolitan Lima population of over 18 years, specifically socioeconomic levels B and C in the districts of Barranco, La Molina, Miraflores, San Borja and Santiago de Surco because this population sectors have the greatest purchasing power. The location of the plant will be in the department of Lima, specifically in the province of San Vicente de Cañete due to many factors, mainly the proximity to Quebranta grapes because they can’t remain for more than 8 hours in the crates and their sugar content will be gradually reduced and proper fermentation won’t be achieved. The selected location has the ideal conditions for supplying electricity and potable water, which are essential for the development of the project, as well as the adequate availability of workforce and machinery.